2020
DOI: 10.3347/kjp.2020.58.3.257
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and B1 gene Phylogeny of Toxoplasma gondii of Dogs and Cats in Republic of Korea

Abstract: The outbreak of human toxoplasmosis can be attributed to ingestion of food contaminated with Toxoplasma gondii. Toxoplasmosis recently increased in domestic and stray dogs and cats. It prompted studies on the zoonotic infectious diseases transmitted via these animals. Sero- and antigen prevalences of T. gondii in dogs and cats were surveyed using ELISA and PCR, and B1 gene phylogeny was analyzed in this study. Toxoplasmosis antibodies were measured on sera of 403 stray cats, 947 stray dogs, 909 domesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Further phylogenetic analyses are needed to distinguish between types I and III more clearly. In other studies, infected cats also exhibited types I, II, and III in South Korea [45,46]. Since intake of oocyst-contaminated water or food is the only effective way to get infected with T. gondii, the low prevalence of cats with T. gondii oocysts in South Korea may decrease the worry and public awareness of cats as the main cause for human transmission of toxoplasmosis [44].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Further phylogenetic analyses are needed to distinguish between types I and III more clearly. In other studies, infected cats also exhibited types I, II, and III in South Korea [45,46]. Since intake of oocyst-contaminated water or food is the only effective way to get infected with T. gondii, the low prevalence of cats with T. gondii oocysts in South Korea may decrease the worry and public awareness of cats as the main cause for human transmission of toxoplasmosis [44].…”
Section: Discussionmentioning
confidence: 85%
“…Based on the virulence levels of Toxoplasma strains in outbred mice, strains were divided into three genotypes, including types I (highly virulent strain), II (less virulent strain), and III (avirulent strain) [43]. In South Korea, T. gondii has been detected in fecal samples from feral cats (0.9%, 5/563) [44] and stray cats (4.7%, 14/300) [45], blood samples from stray cats (38.9%, 28/72) [6], and blood, fecal, and tissue samples from cats (0.2%, 10/4432) [46]. Seroprevalence of T. gondii infection was reported in cat sitters (6.4%, 43/673) and people (8.0%, 89/1114) in South Korea [47].…”
Section: Discussionmentioning
confidence: 99%
“…Considering that dogs and cats can be involved in the maintenance of the urban and periurban life cycle of T. gondii, and that they usually share the same areas within cities, serological surveys in both species are the key aspect to address control strategies of this zoonotic pathogen, especially in areas where there are colonies of free-roaming dogs and cats in close contact with humans (Fábrega et al, 2020;Park et al, 2020). In fact, this health concern is reflected in various studies of T. gondii seroprevalence in dogs and cats previously conducted in several areas around the world from a One Health perspective (Rengifo-Herrera et al, 2017;Cong et al, 2018;de Oliveira et al, 2019;Park et al, 2020). In this respect, serological survey studies provide valuable information that allows us to know the contact of host species with T. gondii and, indirectly, to interpret the epidemiological risk that the presence of these animals implies for the human population (Ding et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In our study, PCR analysis of the Toxoplasma B1 gene was found only in two samples (0.7%) that were positive for B1. However, this result is not without precedent; in a study in Korea, 1312 samples of cat blood were analysed using the same B1 gene with PCR method, identifying only five positive samples [15]. The two samples positive by PCR were also positive by Western blot; this is possibly due to tachyzoites in blood by acute infection and low sensitivity of PCR [15,16].…”
Section: Discussionmentioning
confidence: 99%